Thermal conductivity of solid krypton with methane admixture: Low-Temperature Physics and Chemistry in Cryomatrice - Dudkin, V. V.; Gorodilov, B. Ya.; Krivchikov, A. I.; Manzhelii, V. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The thermal conductivity of CH4-Kr solid solutions is investigated at CH4 concentrations 0.2√5.0% in the temperature range 1.8√40 K. It is found that the temperature dependence of the thermalconductivity has features typical of resonance phonon scattering. The analysis of the experimentalresults shows that the main contribution to the impurity-caused scattering of phonons is made by the scattering on rotational excitations of the nuclear spin T-species of CH4 molecules. The phonon-rotation interaction parameter is estimated.